Kontribusi Fintech Syariah dalam Pengembangan UMKM di Masa Pandemi COVID 19 - Anna Sardiana Ali (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2022)
The obstruction of several business activities caused by the pandemic has led to the need for institutions that can manage and develop MSMEs in the midst of this outbreak. One of the institutions that is being developed is Sharia fintech. This research uses a literature study method where in this method the researcher uses several sources that present topics related to the research. This research also uses secondary sources where the source presents data related to Sharia fintech and MSMEs. The research technique used in this study is descriptive statistics by examining patterns to develop MSMEs using Sharia-based fintech. The results of this study revealed that currently the total assets of Sharia fintech reached 50 billion in IDR with a growth 8.32 %, which shows a significant figure compared to February 2020. Since the development of Sharia fintech, there have been 13 Sharia financial technology and there’re six companies engaged in financing 65 to develop MSMEs. The pattern used in developing MSEs that have a Sharia basis can use the role of fintech institutions not only providing financial assistance in the form of money but also providing assistance in the form of companions in developing their businesses related to MSME marketing..